A Randomized Crossover Study Comparing a Novel Needle Guidance Technology for Simulated Internal Jugular Vein Cannulation. (September 2015) - Auyong, David B.; Yuan, Stanley C.; Rymer, Alyse N.; Green, Cynthia L.; Hanson, Neil A.
<x xml:space="preserve">Abstract</x> Background: Despite ultrasound guidance for central line placement, complications persist, as exact needle location is often difficult to confirm with standard two-dimension ultrasound. A novel real-time needle guidance technology has recently become available (eZono, Germany) that tracks the needle during insertion. This randomized, blinded, crossover study examined whether this needle guidance technology improved cannulation of a simulated internal jugular (IJ) vein in an ultrasound phantom. Methods: One hundred physicians were randomized to place a standard needle in an ultrasound neck phantom with or without the needle guidance system. Video cameras were placed externally and within the lumens of the vessels to record needle location in real time. The primary outcome measured was the rate of posterior wall puncture. Secondary outcomes included number of carotid artery punctures, number of needle passes, final needle position, time to cannulation, and comfort level with this new technology. Results: The incidence of posterior vessel wall puncture without and with needle guidance was 49 and 13%, respectively (P < 0.001, odds ratio [OR] = 7.33 [3.44 to 15.61]). The rate of carotid artery puncture was higher without needle navigation technology than with needle navigation 21 versus 2%, respectively (P = 0.001, OR = 12.97 [2.89 to 58.18]). Final needle tip position being located within the lumen of the IJ was 97% accurate with the navigation technology and 76% accurate with standard ultrasound (P < 0.001, OR = 10.42 [2.76 to 40.0]). Average time for successful vessel cannulation was 1.37 times longer without guidance technology. Conclusion: This real-time needle guidance technology (eZono) shows significant improvement in needle accuracy and cannulation time during simulated IJ vein puncture.